(3CSGei GdcJH GdWHjI eY eUfjagGs
(3ChdgG (B:s
(3cJGH cGed GdUfGYI GdWHjI dYdi Hf GdYHGS s
(3BNQgG (B:s
(3cJGH MOhO GdCeQGV LeY CHj GdeLO GdWHjH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG Jedc jQLY Edi SfI (B1207 (3g` HGSe jhSa Hf jhSa eQRQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI HZOGO (B_ (3eYgO GdOQGSGJ GdESdGejI GdYdjG (B(404) s
Keywords: (3GdeLGejYs